2012
DOI: 10.1021/ct200618b
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the vdW-TS Method for Extended Systems

Abstract: The Tkatchenko-Scheffler vdW-TS method [Phys. Rev. Lett.2009, 102, 073005] has been implemented in a plane-wave DFT code and used to characterize several dispersion-dominated systems, including layered materials, noble-gas solids, and molecular crystals. Full optimizations of the structures, including relaxation of the stresses on the unit cells, were carried out. Internal geometrical parameters, lattice constants, bulk moduli, and cohesive energies are reported and compared to experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 83 publications
8
113
0
Order By: Relevance
“…Compared to PBE, which is known to often substantially overestimate lattice constants, 29 both the pairwise and many-body approaches give good agreement with experiment, with many of the differences likely to be of the order of zero-point and thermal vibrational contributions to the lattice constants. The estimation of these contributions for any crystal is non-trivial and will form part of our future work in this area.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Compared to PBE, which is known to often substantially overestimate lattice constants, 29 both the pairwise and many-body approaches give good agreement with experiment, with many of the differences likely to be of the order of zero-point and thermal vibrational contributions to the lattice constants. The estimation of these contributions for any crystal is non-trivial and will form part of our future work in this area.…”
Section: Discussionmentioning
confidence: 80%
“…Hybrid functionals are often not used in the study of cohesive properties of molecular crystals, 29,30 largely due to their additional computational cost, which particularly in a plane-wave basis can reach more than an order of magnitude larger than the corresponding semi-local functional. The present database of crystals suggests that hybrids may be important for accurate work.…”
Section: Role Of Exact Exchangementioning
confidence: 99%
See 2 more Smart Citations
“…As a result, it often fails to describe the intermolecular interaction and phenomena arising from it (e.g., sublimation and physisorption). It has been shown that a proper vdW correction can significantly improve the performance of conventional DFT, greatly extending its applicability to a broader class of problems such as molecular complexes and solids [2][3][4][5][6][7][8][9] and layered materials. 10,11 The vdW interaction is an important long-range nonlocal correlation arising from instantaneous charge fluctuations on each density fragment.…”
mentioning
confidence: 99%